Acute fulminant myocarditis in scrub typhus - Sittiwangkul R. (2014)
Scrub typhus is a zoonotic disease caused by Orientia tsutsugamushi in which humans are accidental hosts. It is a febrile illness which is confined to rural Asia and the Western Pacific islands. Severe complications are very rare. We report four cases of acute fulminant myocarditis in children with scrub typhus. This complication led to severe cardiogenic shock and death in two of them. We believe this is the first report of fulminant myocarditis complicating scrub typhus in children. © 2008 The Liverpool School of Tropical Medicine.